Characterization of Distributions Through Stochastic Models Under Fuzzy Random Variables (Journal of Nonlinear Modeling and Analysis, 2025)
This paper is noteworthy because it investigates a novel methodfor comparing the expectations of stochastic models in fuzzy contexts. Actuarial science and economics both depend on stochastic models. Understandingthe novel concepts of stochastic comparison of stochastic models based on theexponential order is the main advantage of this study. We solved the preservation properties and theorem, created a new definition, and put the fuzzy meaninactive time order definition into practice. Stochastic models are handled ina variety of applications.
Keywords: Fuzzy set; random variables; stochastic orders.